Carcinoma of the breast in low resource setting: A surgical case series from rural India - Royson Dsouza; Anish Jacob; Mrudula Rao; Nandakumar Menon (Health for All Nations, 2021)
The burden of breast cancer has been on the rise world over and has become the most common cancer among women in urban India and the second most common cancer in rural women after carcinoma cervix. There is a considerable delay in presentation, associated with a lack of access to adequate and timely surgical intervention. Consequently, most patients present to tertiary care centers in advanced or inoperable stages. Many subsets of these patients can be managed adequately in resource-limited rural surgical centers. In this series of patients diagnosed with carcinoma breast, we have outlined comprehensive management possible in resource-constrained settings. The challenges in adhering to the standard of care and strategies to overcome these limitations have been discussed with a relevant review of the literature.